What does Klinefelter syndrome mean for men with azoospermia in Japan? - Fumi Atogami; Noriko Yamaguchi; Yasuka Nakamura; Toyoko Yoshizawa (Mashhad University of Medical Sciences, 2018)
Background & aim: The aim of this study was to explore the men's perceptions of being diagnosed with Klinefelter syndrome. Methods: This qualitative study was conducted on five azoospermic men diagnosed with Klinefelter syndrome referring to two special infertility treatment clinics for males in Japan. The paqrticipants were selected through purposive sampling technique.The data were collected by semi-structured interviews within April 2013 to March 2015 and analyzed using a thematic analysis approach. Results: The analysis of the data resulted in the emergence of four themes, including 'I cannot understand my diagnosis', 'the cause of my azoospermia was identified', 'I do not have any other healthcare problems besides Klinefelter syndrome', and 'Klinefelter syndrome means that I am more likely to have viable sperm'. Through these themes, we found that azoospermic men considered their diagnosis of the chromosomal disorder as good news; and as a reason for their infertility which might not affect their lives. Furthermore, they believed that having Klinefelter syndrome means that they are more likely to have their own child. Conclusion: The men diagnosed with Klinefelter syndrome had various feelings about their diagnosis. They were hopeful about the outcome of undergoing micro dissection testicular sperm extraction (Micro-TESE). These findings are useful for healthcare workers and could raise their awareness; as they understand that those men with Klinefelter diagnosis have higher expectations regarding micro-TESE.